2007
DOI: 10.1111/j.1532-950x.2007.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and Chemokine Gene Expression of IL‐1β Stimulated Equine Articular Chondrocytes

Abstract: Chondrocytes express proinflammatory cytokines and chemokines capable of modulating a local inflammatory cascade in articular cartilage, which could potentially lead to focal degradation and osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 35 publications
4
33
2
4
Order By: Relevance
“…This could be explained by MDA role in stabilization of collagen via MDA crosslinking that encourages more excessive glycation which start further lipid peroxidation. Moreover, as previously reported by [28] high MDA can induce many inflammatory cytokines. These cytokines trigger others production and lead to more oxidative stress [29].…”
Section: Discussionmentioning
confidence: 61%
“…This could be explained by MDA role in stabilization of collagen via MDA crosslinking that encourages more excessive glycation which start further lipid peroxidation. Moreover, as previously reported by [28] high MDA can induce many inflammatory cytokines. These cytokines trigger others production and lead to more oxidative stress [29].…”
Section: Discussionmentioning
confidence: 61%
“…Recent evidence has shown that OA also has an inflammatory component (Berenbaum, 2013;Konttinen et al, 2012), where matrix fragments can signal through toll-like receptors. Proteolytic degradation of the matrix can also release immobilised cytokines such as interleukin (IL)-1β and IL-6 and tumour necrosis factor (TNF) which in turn further induce cytokine expression and secretion of matrix-degrading enzymes from chondrocytes, thus propagating tissue breakdown (David et al, 2007;Martel-Pelletier, 1999). These effects are largely mediated by nuclear transcription factors such as nuclear factor-kappaB (NF-κB), which has been shown to induce expression of inflammatory cytokines, matrix metalloproteinases (MMPs), cyclooxygenase-2 (COX-2), as well as adhesion molecules (ICAM-1, VCAM-1 and E-selectin) implicating NF-κB in the recruitment of leukocytes (Ke et al, 2007;Miagkov et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Some cytokines can control the release of other cytokines. This event leads to increased oxidative stress in chronic inflammations (Chokkalingam et al, 2013;David et al, 2007;Vlahopoulos et al, 1999).…”
Section: Cytokinesmentioning
confidence: 95%